Theodore Lowi’s Public Policy Types Theory - Asryan, Narine (YSU Journal of International Affairs, 2021)
The article discusses the policy types theory of the American political theorist T. Lowi: in particular, four types of public policy proposed by the author are carefully studied: redistributive, regulatory and constituent policies, and critical approaches of other political theorists (P. Steinberger, J. Anderson, A. Kellow) to the theory are discussed. The article also presents other approaches to the interpretation of such concepts as the political environment, the political process, the outputs and outcomes of public policy.
Keywords: public policy; political environment; political system; political process; policy output; politics outcome; policy type; regulatory policy; redistributive policy; constituent policy